Isothermal and Thermal Analyses of Elastohydrodynamic Lubrication of Hard Rolling Contact - Abdel Malik, Mohamed A. H. (1997)
In the field of industrial tribology, elastohydrodynamic lubrication (EHL) is a comparatively recent area of research. It only became properly established in the early 1960s. EHL of rolling contact is mainly divided to two phases (soft and hard), depending on the elasticity modulus of the material in contact. Hard rolling which relates to materials of high modulus of elasticity e.g. metal, is the part of interesting the present study. The f1rst objective of the research is to study the elastohydrodynamic rolling line contact. lubr1cat1on problem of hard Second is to investigate the isothermal and thermal conditions for EHL in hard rolling system. The contact geometry of the rolling process was specified as a line contact. An in compressible fluid flows in to the system. Under both isothermal and thermal conditions, a Newton1an lubricant was descr1bed. Two different widely used lubricants were tested. First, is a mineral Naphthenic (TN22) and the second is asynthetic Cycloaliphatic (ST40). It is assumed that two rollers of equal radius are moving relatively with same speed on a plane of d1fferent velocity. Two coord1nate axe s were considered (x and y). The parameters and conditions of controlling the system of contact are theoretically selected to match the practical field situations. Newton-Raphson and the finite difference methods were represented in the mathematical technique used for computations.